STUDY OF THE PLACES OF DEPOSITION AND WAYS OF DISTRIBUTION OF THE ANESTHETIC SOLUTION OVER THE ANATOMICAL STRUCTURES ADJACENT TO THE LOWER JAW DURING MANDIBULAR ANESTHESIA - Anisimov, M.V.; Shnayder, S.A.; Anisimova, L.V.; Skrypnykov, P.M.; Reyzvikh, O.E. (World of Medicine and Biology, 2021)
The problem of unstable quality of dental pulp anesthesia during mandibular anesthesia is very relevant in modern dentistry, since this method of local anesthesia is the most common for all types of dental treatment in the lower jaw, as well as for outpatient surgical interventions. Several dozen intraoral and extraoral variants of mandibular anesthesia are known. The main criterion for the effectiveness of mandibular anesthesia is considered to be anesthesia of the dental pulp. An interesting fact is that the axons that provide sensitivity to the pulp of the teeth, located in the center of the nerve, and therefore some of the latter are saturated with anesthetic solution. The anatomical part of the study – 21 sagittal cut of the human head, was carried out on the basis of the Department of human anatomy of the Odessa National medical University; X-ray part of the study – tomograms with a radiopaque substance of 6 sagittal cuts of the human head, was carried out on the basis of a private diagnostic center, which is equipped with a Somatom Definition AS tomograph from “Siemens” company. X-ray contrast substance “Verografin” was injected in a volume of 1.7 ml for each sagittal cut of the human head. The studies were carried out in the period 2013–2014 years.
Keywords: local anesthesia; conduction anesthesia; tomography; anatomical structure of the trigeminal nerve